2021
DOI: 10.1111/bph.15335
|View full text |Cite
|
Sign up to set email alerts
|

Activation of trace amine‐associated receptor 1 selectively attenuates the reinforcing effects of morphine

Abstract: Background and Purpose Trace amine‐associated https://www.guidetopharmacology.org/GRAC/ObjectDisplayForward?objectId=3641 receptors play critical roles in regulating dopamine transmission. Previous studies showed that pharmacologically or genetically manipulating the activity of https://www.guidetopharmacology.org/GRAC/ObjectDisplayForward?objectId=3641 receptors modulates addiction‐like behaviours associated with psychostimulants. However, little is known about whether https://www.guidetopharmacology.org/GRAC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 49 publications
1
8
0
Order By: Relevance
“…The increased discrimination ratio of RO5263397 treatment group was not likely due to potential sedative effect of the treatment, since the doses (0.03 and 0.1 mg/kg) of RO5263397 used in the present study were shown not to affect the locomotor activity in our previous studies (Liu et al 2021;Wu et al 2020). Thus, it is not possible that mice that showed less time exploring the familiar object in the RO5263397 group were due to decreased locomotion caused by the treatment.…”
Section: Discussionsupporting
confidence: 42%
See 2 more Smart Citations
“…The increased discrimination ratio of RO5263397 treatment group was not likely due to potential sedative effect of the treatment, since the doses (0.03 and 0.1 mg/kg) of RO5263397 used in the present study were shown not to affect the locomotor activity in our previous studies (Liu et al 2021;Wu et al 2020). Thus, it is not possible that mice that showed less time exploring the familiar object in the RO5263397 group were due to decreased locomotion caused by the treatment.…”
Section: Discussionsupporting
confidence: 42%
“…The enhancement of novel object recognition induced by RO5263397 was dependent on TAAR1. Firstly, the partial agonist RO5263397 was shown to be highly selective on TAAR1 as it demonstrated high affinity at mouse, rat, and human TAAR1 expressed in HEK293 cells but not many other receptors (Liu et al 2021;Revel et al 2013). Meanwhile, while RO5263397 increased the firing rate of VTA dopamine and dorsal raphe nucleus (DRN) 5-HT neurons in WT mice, it did not affect the firing frequency in slices from Taar1 −/− mice, demonstrating a TAAR1-specific effect Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It plays a crucial role of negatively regulating dopamine transmission and thus is widely involved in drug addiction 58,59 . In fact, previous studies have shown that activation of TAAR1 attenuates cocaine, methamphetamine, morphine and nicotine self‐administration, cue‐ and drug‐induced reinstatement and ethanol‐ and nicotine‐induced behavioural sensitization 26,29,30,60–62 . Moreover, in our recent study, we showed that TAAR1 agonists were able to reduce the positive reinforcing effects of nicotine by extensive behavioural assay including nicotine self‐administration, behavioural sensitization, nicotine discrimination and cue‐ and drug‐induced reinstatement 30 .…”
Section: Discussionmentioning
confidence: 85%
“…did not affect the naltrexone-induced jumping behaviour and conditioned place aversion (CPA) in morphine-dependent mice. 60 In addition, the fact that RO5263397 alone did not affect the analgesic effect of morphine 60 while remarkably reduced mechanic hypersensitivity in LA rats after abstinence suggest the effect of RO5263397 on nociception is dependent on the progressive neuroadaptations involved in nicotine withdrawal. Moreover, the effects of RO5263397…”
Section: Discussionmentioning
confidence: 99%